Dust-obscured Galaxies with Broken Power-law Spectral Energy Distributions Discovered by UNIONS - Taketo Yoshida; Tohru Nagao; Yoshiki Toba; Akatoki Noboriguchi; Kohei Ichikawa; Hendrik Hildebrandt; Naomichi Yutani; Kenneth C. Chambers; Ryo Iwamoto; Seira Kobayashi; Masamune Oguri; Ken Osato; et al. (The Astrophysical Journal, 2025)
We report on the spectral energy distributions (SEDs) of infrared (IR)-bright dust-obscured galaxies (DOGs) with ( i − [22]) _AB ≥ 7.0. Using photometry from the deep and wide Ultraviolet Near-Infrared Optical Northern Survey, combined with near-IR (NIR) and mid-IR data from the UKIRT Infrared Deep Sky Survey and the Wide-field Infrared Survey Explorer, we successfully identified 382 DOGs in ∼170 deg ^2 . Among them, the vast majority (376 DOGs) were classified into two subclasses: bump DOGs (132/376) and power-law (PL) DOGs (244/376), which are dominated by star formation and active galactic nuclei (AGNs), respectively. Through the SED analysis, we find that roughly half (120/244) of the PL DOGs show broken power-law (BPL) SEDs. The significant red slope from optical to NIR in the SEDs of these “BPL DOGs” probably reflects their large amount of dust extinction. In other words, BPL DOGs are more heavily obscured AGNs, compared to PL DOGs with non-BPL SEDs.